2008
DOI: 10.1080/03098770802395587
|View full text |Cite
|
Sign up to set email alerts
|

Towards a pedagogy for clinical education: beyond individual learning differences

Abstract: The development of teaching in higher education towards a more learnerorientated model has been supported by the literature on individual learning differences and on learning styles in particular. This has contributed to the evolution of university pedagogy away from a medieval transmission model than runs counter to contemporary understanding of learning. However, rather than solving problems of classroom practice, recognition of student learning differences has amplified a number of tensions within the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…The study also identified a chain structured concept map, which disguised the potential expert networks of understanding possessed by a pharmacist. Kinchin et al (2008a, b) reported that experts, depending on the situational context, alternate between chains of practice and networks of understanding. For practical purposes, experts will often employ linear chains of practice to ensure that a task is executed with efficiency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study also identified a chain structured concept map, which disguised the potential expert networks of understanding possessed by a pharmacist. Kinchin et al (2008a, b) reported that experts, depending on the situational context, alternate between chains of practice and networks of understanding. For practical purposes, experts will often employ linear chains of practice to ensure that a task is executed with efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, concept mapping is a useful tool for reflecting on current knowledge and targeting training needs. Within dentistry, concept maps developed by teachers have been used to train undergraduate students to perform clinical skills (Kinchin et al 2008a, b;Kinchin and Cabot 2009). This has enabled the teacher to convey their expert tacit knowledge of a clinical skill to the undergraduates, thereby promoting deep and holistic learning.…”
Section: Discussionmentioning
confidence: 99%
“…It did, however, yield articles offering expert input. First, there were articles that addressed the application of individualized instruction (also known as student-centered learning) to medical education (Newble & Gordon 1985;Newble & Entwistle 1986;McManus et al 1998;Hassler 2005;Kinchin et al 2008;Lacasse et al 2009) and general adult education (Coffield et al 2004;Cuthbert 2005;Lalley & Gentile 2009). In addition, several articles characterized the needs and actions of trainees at different levels on attending rounds (Foley et al 1979; Shulman et al 1992;Elliot & Hickam 1993;Ways et al 1996;Hoellein et al 2007;Castiglioni et al 2008;Tariq et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The development of university pedagogy needs to consider the nature of expertise and how this can be modelled for students in such a way that teaching reflects the values of each academic discipline (Kinchin, Baysan, and Cabot 2008). This development aims to find a practical solution to the constraints within the system that tend towards the maintenance of the status quo, by challenging the 'safe systems' that have dominated the development of university pedagogy (Canning 2007) that can result in cycles of non-learning that embody the antithesis of the purpose of higher education (Kinchin, Lygo-Baker, and Hay 2008).…”
Section: Introductionmentioning
confidence: 99%